2021
DOI: 10.1302/0301-620x.103b5.bjj-2020-1393.r2
|View full text |Cite
|
Sign up to set email alerts
|

Repeat limited fasciectomy is a safe and effective treatment for recurrence of Dupuytren’s disease

Abstract: Aims The results of surgery for Dupuytren’s disease can be compromised by the potential for disease recurrence and loss of function. Selecting which patients will benefit from repeat surgery, when to operate, and what procedure to undertake requires judgement and an understanding of patient expectations and functional needs. We undertook this study to investigate patient outcomes and satisfaction following repeat limited fasciectomy for recurrent Dupuytren’s disease. Methods We prospectively identified all pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“… 17 Several studies have reported the factors that predict disease development or surgical treatments for Dupuytren’s contracture. 18 , 19 However, its pathogenesis remains unclear. Although the mechanism underlying fibrosis of the palmar aponeurosis has yet to be identified, TGF-β signalling, which plays an important role in fibrosis, has been implicated.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Several studies have reported the factors that predict disease development or surgical treatments for Dupuytren’s contracture. 18 , 19 However, its pathogenesis remains unclear. Although the mechanism underlying fibrosis of the palmar aponeurosis has yet to be identified, TGF-β signalling, which plays an important role in fibrosis, has been implicated.…”
Section: Discussionmentioning
confidence: 99%
“…DF involves removal of fibrous tissue and skin with the application of a full thickness skin graft. Disadvantages of DF include prolonged recovery, skin graft failure, donor sight scarring, higher complication rates, and cosmetic irregularities [14][15][16] .…”
Section: Superficial Fibroma and Fibromatosismentioning
confidence: 99%
“…Ultrasound images of fibromatosis show hypoechoic nodules/cords originating in the palmar fascia. MRI scanning shows low signal intensity in both T1 and T2 images, characteristic of collagen-dense nodules/cords 15,16 . Treatment options for Dupuytren's disease consists of conservative therapy (physiotherapy, radiation, steroid [oral vs. injections] Clostridium histolyticum collagenase [CCH] and surgical options [percutaneous needle fasciotomy, open fasciotomy [OF], limited fasciectomy [LF], and dermofasciectomy [DF]).…”
Section: Superficial Fibroma and Fibromatosismentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that both treatment modalities are associated with favorable levels of patient satisfaction. According to Shaw et al, CCH injections are seen to be more effective in mild and moderate disease [ 43 ], unlike LF, which is seen to be more beneficial in aggressive and recurrent disease [ 44 , 45 ].…”
Section: Reviewmentioning
confidence: 99%